2016
DOI: 10.1096/fj.201600746r
|View full text |Cite
|
Sign up to set email alerts
|

miR‐184 exhibits angiostatic properties via regulation of Akt and VEGF signaling pathways

Abstract: Corneal avascularity is critical for achieving transparency necessary for proper transmission of light to the lens and visual acuity. Although much is known about angiogenesis and angiostasis, the precise regulation of these processes in the cornea is unclear. MicroRNA (miR)-184, the most abundant corneal epithelial miRNA, has been suggested to function in corneal angiostasis by altering VEGF signaling; however, the mechanism(s) underlying this regulation have not been addressed. Using a combination of in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…Researches showed that miR‐184 can inhibit CNV by attenuating both VEGF and Akt signaling. It can suppress the proangiogenic factors, friend of Gata 2, phosphatidic acid phosphatase 2b and platelet‐derived growth factor (PDGF)‐β directly . However, there were experiments showing that the expression of miR‐21 increased significantly compared with the healthy cornea at 4 and 7 days after alkali burn.…”
Section: The Drug Treatment Of Cnvmentioning
confidence: 99%
“…Researches showed that miR‐184 can inhibit CNV by attenuating both VEGF and Akt signaling. It can suppress the proangiogenic factors, friend of Gata 2, phosphatidic acid phosphatase 2b and platelet‐derived growth factor (PDGF)‐β directly . However, there were experiments showing that the expression of miR‐21 increased significantly compared with the healthy cornea at 4 and 7 days after alkali burn.…”
Section: The Drug Treatment Of Cnvmentioning
confidence: 99%
“…Alternatively, downregulation of miR-4516, may present an attempt of the diabetic stromal cells to preserve normal wound healing, which may be eventually counteracted by other miRs that become elevated in diabetes, for instance, miR-146a that inhibits wound healing-stimulating EGFR 48 . Interestingly, miR-184, the most abundantly expressed miRNA in central corneal epithelium 49 , 50 is among the top differentially expressed miRNAs and is significantly upregulated in DM-Exos. Its key role in corneal epithelial homeostasis has been shown in several studies 50 52 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-184 negatively modulates Wnt signaling both in vivo and in vitro ( Takahashi et al 2015 ). MiR-184 could inhibit protein expression in human trabecular meshwork cell cytotoxicity, apoptosis, and extracellular matrix via targeting HIF-1α in vivo , and it can also exhibit angiostatic properties through regulating signaling pathways including Akt, TNF-α, and VEGF ( Park et al 2017 ; Wang et al 2017 ). All the results mentioned above showed that Aja-miR-184 may be crucial to the stress response in sea cucumbers by regulating genes related to autophagy, oxidative damage, and cell proliferation under hypoxia stress.…”
Section: Discussionmentioning
confidence: 99%